Application program learning based on android for students experiences - Aminudin, Nur; ., Fauzi; Huda, Miftachul; Hehsan, Aminudin; Nasir Ripin, Mohd.; Haron, Zulkifli; Junaidi, Juhazren; Irviani, Rita; Muslihudin, Muhamad; Hidayat, Syahromi; Maseleno, Andino; Gumanti, Miswan; et al. (International Journal of Engineering and Technology, 2018)
With the advancement of the era that increasingly rapidly affect the pattern of all-dependent life with advanced technology that allows us to do many things in everyday life in accordance with our needs such as using gadgets as a medium of learning. By using Android based gadgets we can use it to learn to play guitar that is supported by the Android application program that presents learning about playing guitar. Using gadgets as a medium of learning is an interesting and very easy. Android application program about learning to play the guitar is facilitate us in learning. Gadget as a medium of learning is an utilization technological developments that are worth positive and useful for us. Android guitar application presents about the correct guitar playing procedure and there chord and chord sound, not only see the chord form but we can listen to chords. Application made using prototyping method so that will continue to be fixed when there are deficiencies. This application will continue to grow in accordance with the needs of the user. This application is made to facilitate the learning process. Application users will continue to be developed to fit the needs of users and become the right facilities and useful for its users.Â Â